2016
DOI: 10.12659/msm.896047
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNA/mRNA-Negative Regulation Pairs in Nasopharyngeal Carcinoma

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is a common malignancy in South-East Asia. NPC is characterized by distant metastasis and poor prognosis. The pathophysiological mechanism of nasopharyngeal carcinoma is unknown. This study aimed to identify the crucial miRNAs in nasopharyngeal carcinoma and their target genes, and to discover the potential mechanism of nasopharyngeal carcinoma development.Material/MethodsMicroarray expression profiling of miRNA and mRNA from the Gene Expression Omnibus database was dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
(50 reference statements)
1
15
0
Order By: Relevance
“…Silencing of miR-632 inhibits EMT (epithelial-mesenchymal transition) and eliminates invasive ability in breast cancer cells. In addition, miR-632 is related to nasopharyngeal carcinoma, laryngeal cancer and myelodysplastic syndrome [1618]. Tuberculosis risk may be influenced by miR-632-mediated regulation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Silencing of miR-632 inhibits EMT (epithelial-mesenchymal transition) and eliminates invasive ability in breast cancer cells. In addition, miR-632 is related to nasopharyngeal carcinoma, laryngeal cancer and myelodysplastic syndrome [1618]. Tuberculosis risk may be influenced by miR-632-mediated regulation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although endometriosis is considered a nonmalignant condition, the characteristics of endometriosis such as infiltration of endometriosis tissues to surrounding organs and presence of angiogenesis resembles a tumour-like behavior to some extent [18, 28, 29]. Microarray studies including ours demonstrated that FJX1 is overexpressed in NPC relative to noncancerous tissues [13, 30, 31]. Overexpression of FJX1 in the transcriptomic level was also observed in RNA-Seq data from 43 head and neck cancers compared to matched normal samples from the TCGA database.…”
Section: Discussionmentioning
confidence: 96%
“…In gastric cancer, DTX1 was reported specifically down-regulated and promoted cellular FLICE inhibitory protein (c-FLIP), as its E3 ligase substrate, to degrade through the endosome-lysosomal pathway 25 . DTX4 was significantly up-regulated through comparison of the interaction network between miRNAs and target genes in nasopharyngeal carcinoma samples 26 .…”
Section: Discussionmentioning
confidence: 99%